Clonal variation based on some morphological and micromorphological characteristics in the Boyabat (Sinop/Turkey) black pine (Pinus nigra subsp. pallasiana (Lamb.) Holmboe) seed orchard - Yigit, Nurcan; Ozturk, Ayse; Sevik, Hakan; Özel, Halil Barış; Kshkush, Fathi Elmabruk Ramadan; Isik, Berkant (BioResources, 2023)
Seed orchards with high hereditary qualities and the improvement studies used are of great importance. This study was carried out on individuals in a Boyabat grafted black pine seed orchard, Sinop. The morphological and micromorphological measurements of the characteristics were performed on needle samples taken from individuals, and the genetic diversity was determined on a clonal basis. According to the analysis of variance applied to the data obtained from the measurements and the morphological and micromorphological characters of the clones, it was determined that there was a significant difference among the clones at the P<0.001 confidence level. In this context, according to Duncan’s Range test, the creation of a large number of groups is an indicator of it. The highest heritability rates were obtained in needle diameter, stipule diameter, number of the dorsal stoma, and needle length characteristics.
Keywords: Morphology; boyabat; Clones; seed orchard; clonal variation; clones; morphology; Black Pine; Boyabat; black pine; Seed Orchard; TP248.13-248.65; Biotechnology; 15. Life on land